Islamic Republic of Iran : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper discusses some options to strengthen Iran's fiscal framework, and highlights the need for a medium-term framework. Fiscal policy design in Iran faces numerous challenges. Some are current, such as managing volatile oil revenue while addressing development needs. Other challenges are related to demographic pressures from new entrants to the labor market, as the country needs to prepare from aging pressures in the decades to come. With medium-term planning, macroeconomic stability, and adequate spending, fiscal policy could play a critical role in fostering growth. Ultimately, addressing these issues would help Iran achieve its objective of becoming one of the fastest-growing emerging economies.